The impact of a nutrition-sensitive graduation model program on child nutrition: Experimental evidence from Ethiopia - Hirvonen, Kalle; Leight, Jessica; Gilligan, Daniel O.; Mesfin, Hiwot Mekonnen; Mulford, Michael; Tesfaye, Haleluya (International Food Policy Research Institute, 2025)
Multifaceted graduation models are a promising strategy to sustainably reduce poverty, yet evidence on their effects on child undernutrition remains limited. This randomized controlled trial evaluated a nutrition-sensitive graduation model combining village economic and savings associations, peer-led behavior change communication, and maternal cash transfers (and for a subset, lump-sum livelihoods transfers) implemented among ultra-poor households in rural Ethiopia. The model without maternal cash transfers improved maternal nutrition knowledge and financial inclusion but did not generate meaningful changes in children’s diets or growth. Supplementing the pro-gram with maternal cash transfers produced at least moderate improvements in child diet quality, early childhood development, household consumption, and assets. The largest improvements in child growth occurred among households receiving both the livelihoods grant and maternal cash transfers. Overall, the results suggest that coupling behavior change communication and livelihoods support with sufficient financial support is critical for achieving meaningful progress in both economic well-being and child nutrition.